2020
DOI: 10.3390/beverages6020026
|View full text |Cite
|
Sign up to set email alerts
|

Ready to Use Therapeutical Beverages: Focus on Functional Beverages Containing Probiotics, Prebiotics and Synbiotics

Abstract: The growing global interest in functional foods containing nutrients capable of adding possible beneficial health effects is rapidly increasing both interest and consumer demand. In particular, functionalized beverages for their potential positive effect on health e.g., decreasing cholesterol level, lowering sugar, high fiber content, ability to enhance the immune system, and help digestion, have recently received special attention. Among the different beverages available on the market, probiotic dairy and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 157 publications
0
29
0
Order By: Relevance
“…In the last decades, many scientific reports highlighted nutritional properties of kefir and health benefits owing to its antimicrobial, anticancer, gastrointestinal tract effects, gut microbiota modulation, cholesterol-lowering activity, and anti-diabetic effects [ 3 , 6 , 7 , 8 , 9 ]. Recently, milk consumption has been declining, and consumer demand for cow’s milk alternatives increased as a result of the increase in the diagnosis of lactose intolerance, allergies, and cholesterol issues [ 10 , 11 , 12 , 13 ]. Furthermore, the ongoing trend of vegetarianism, with an increasing number of vegan/vegetarian consumers, has established a massive worldwide importance of non-dairy plant-based dairy substitutes [ 10 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, many scientific reports highlighted nutritional properties of kefir and health benefits owing to its antimicrobial, anticancer, gastrointestinal tract effects, gut microbiota modulation, cholesterol-lowering activity, and anti-diabetic effects [ 3 , 6 , 7 , 8 , 9 ]. Recently, milk consumption has been declining, and consumer demand for cow’s milk alternatives increased as a result of the increase in the diagnosis of lactose intolerance, allergies, and cholesterol issues [ 10 , 11 , 12 , 13 ]. Furthermore, the ongoing trend of vegetarianism, with an increasing number of vegan/vegetarian consumers, has established a massive worldwide importance of non-dairy plant-based dairy substitutes [ 10 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, 10 6 CFU/g is the most widely accepted minimum concentration of LAB in food [9]. In general, at any time, the bacterial counts were maintained in the samples over level >10 6 CFU/g, which may be attributed to prebiotic fiber content. In fact, HadiNezdah et al demonstrated that flaxseed fiber acts as good prebiotic, enhancing the LAB growth in kefir model [49].…”
Section: The Lactic Acid Bacteria and Fungi Survivability During The mentioning
confidence: 92%
“…The search for new functional food ingredients from natural sources and from by-products represents one of the most important challenges in food science and technology. Food industry by-products represent a valuable source of minerals, proteins, fatty acids, fiber, and bioactive substances, and they can constitute as an important raw material for the development of novel functional foods [ 6 , 7 , 8 ]. Simultaneously, the intake of plant-based products, which are rich sources of bioactive compounds, increases notably [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fermented dairy products, especially kefir, are a rich source of bioactive peptides with antibacterial, antioxidant, and even antihypertensive features, which have a beneficial impact on human health [ 36 , 37 , 38 ]. Polyphenols are another significant group of compounds in fermented products, particularly in alcoholic beverages, and are considered beneficial for humans.…”
Section: Introductionmentioning
confidence: 99%